(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The article describes foreign experience of influence of information technologies on exchange activity of the world; exploitation of the latest technologies in making forecasts in the financial market based on the analysis of search queries on the Internet; and the priority directions of their application on the domestic stock market are determined. After engaging computer systems in stock trading, and later deciding whether to perform computer operations in self-selection and information processing, the concept of algorithmic trading or so-called computer trading was born In order to understand algorithmic trading systems (ie computerized trading), the paper describes the process of trading on the stock exchange on the basis of three stages: pre-trade analysis (processing of information before using data or attracting news to analyze certain features of the market); trading "signal" (choosing the most optimal and profitable asset for bidding) and bidding itself. Pre-trading analysis includes: an alpha model (used to predict the future behavior of financial instruments); risk model and cost model that calculates future costs of trading in financial instruments. The rise of analytically sophisticated computing trading strategies shows that in recent years it has become commonplace for market participants to electronically search for agents and execute a transaction, all of which can be done in seconds. A new style of trading has emerged - high-frequency, where automated systems buy and sell financial instruments on an electronic platform, taking a certain position in just a few seconds. Described as Google search queries, the behavior and emotions of people on social networks can help predict the stock market situation. The conclusion is made. that for capital market companies, technology provides the opportunity to get ahead and win by orienting the process in the right direction, adapting it to the needs of their own businesses.